ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH (PAD) KABUPATEN/KOTA DI PROVINSI JAWA TENGAH TAHUN 2014-2016 - Sitta Nurani Elkhoir, 14.05.52.0090; Darso, Maryono (Students' Journal of Accounting and Banking, 2018)
This study aims to examine the effect of GRDP, Government Expenditures, Population Amounts, Inflation, and Investment affecting the Regional Original Revenue (PAD) in Central Java Province in 2014-2016. This study uses secondary data. The analysis technique used is multiple linear regression analysis. The population in this study contained in the Central Java Province BPS and Central Java Province DPMPTSP in the period 2014-2016. The results of the data analysis showed GRDP, Government Expenditures, Population Amounts, Inflation, Investment simultaneously affect the PAD of Regency / City in Central Java Province in 2014-2016. GRDP, Government Expenditures, Inflation have a significant positive effect, while the population has a significant negative effect and investment has no significant negative effect on PAD. Keywords: PAD, Gross Regional Domestic Product (GRDP), Government Expenditure, Total Population, Inflation and Investment.